2013
DOI: 10.1161/circulationaha.113.001371
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance T 1 Relaxation Time of Venous Thrombus Is Determined by Iron Processing and Predicts Susceptibility to Lysis

Abstract: The source of the T1 signal in the thrombus results from the oxidation of iron (released from the lysis of trapped erythrocytes in the thrombus) to its paramagnetic Fe3+ form. Quantification of T1 relaxation time appears to be a good predictor of the success of thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 31 publications
4
91
1
2
Order By: Relevance
“…Consequently, therapeutic approaches that limit thrombus rbc content may also indirectly reduce thrombus mass and stability. A recent study of experimental thrombosis showed thrombolysis is most effective in aged thrombi containing fewer intact rbc (57). These data suggest thrombus rbc content is a central determinant of thrombolytic success.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, therapeutic approaches that limit thrombus rbc content may also indirectly reduce thrombus mass and stability. A recent study of experimental thrombosis showed thrombolysis is most effective in aged thrombi containing fewer intact rbc (57). These data suggest thrombus rbc content is a central determinant of thrombolytic success.…”
Section: Discussionmentioning
confidence: 96%
“…US has limited usefulness in detection of recurrent DVT and the most promising alternative is MRDTI based on assessment of shortening T1 signal. It is highly accurate for first DVT (64,72).…”
Section: Magnetic Resonance Direct Thrombus Imaging (Mrdti)mentioning
confidence: 99%
“…MRDTI has been shown to be a highly accurate diagnostic test for first DVT. 9,10 The method is based on assessment of a shortening T1 signal. This signal is induced by the paramagnetic methemoglobin, which is being formed in a fresh thrombus.…”
Section: Introductionmentioning
confidence: 99%